A novel circ_0099999/miR-330-5p/FSCN1 ceRNA crosstalk in pancreatic cancer - Yang Wang; Feng Zhang; Dongde Wu; Qun Wang; Lei Nie; Jing Yu (Taylor & Francis Group, 2021)
Background Pancreatic cancer is a lethal malignancy in both sexes throughout the world. Circular RNAs (circRNAs) have been implicated in the development of pancreatic cancer by operating as competing endogenous RNAs (ceRNAs). Here, we explored circ_0099999-mediated ceRNA activity in regulating pancreatic tumorigenesis. Methods Ribonuclease R (RNase R) and subcellular localization assays were utilized to characterize circ_0099999. The levels of circ_0099999, microRNA (miR)-330-5p, and fascin actin-bundling protein 1 (FSCN1) were gauged by quantitative real-time PCR (qRT-PCR) and western blot. Cell proliferation, colony formation, apoptosis, migration, and invasion were evaluated by the Cell Counting Kit-8 (CCK-8), colony formation, flow cytometry, and transwell assays, respectively. The levels of glucose consumption and lactate production were determined using the assay kits. A direct relationship between miR-330-5p and circ_0099999 or FSCN1 was validated by dual-luciferase reporter assay. Tumour xenograft assays were used to analyse the role of circ_0099999 in vivo. Results Circ_0099999 was highly up-regulated in pancreatic cancer tissues and cells. Knockdown of circ_0099999 impeded cell proliferation, migration, invasion, glycolysis, and promoted apoptosis in vitro, as well as diminished tumour growth in vivo. Circ_0099999 targeted miR-330-5p, and miR-330-5p was a downstream mediator of circ_0099999 function. FSCN1 was a direct and functional target of miR-330-5p. Furthermore, circ_0099999 operated as a ceRNA for miR-330-5p to modulate FSCN1 expression. Conclusions Our findings established a novel causal mechanism, circ_0099999/miR-330-5p/FSCN1 ceRNA crosstalk, in regulating pancreatic carcinogenesis and provided that inhibition of circ_0099999 might have therapeutic benefits in pancreatic cancer.